MODEL OF TOLERANCE EDUCATION IN THE TAHFIDZUL QUR’AN AL-KAHFI HIDAYATULLAH ISLAMIC BOARDING SCHOOL IN SURAKARTA, CENTRAL JAVA, INDONESIA - S Suryono; S Sutama; Musa Asy’arie (Profetika: Jurnal Studi Islam, 2020)
This study aims to find out how the tolerance education system has been implemented in the Tahfidzul Qur’an Al Kahfi Hidayatullah Islamic boarding school in Surakarta Indonesia and how the tolerance education method has been applied. The research method used is qualitative. This type of research is a case study in which the research focuses on a particular case to be observed and analyzed thoroughly and thoroughly and the focus of the study is students or students of the Tahfidzul Qur’an Al Kahfi Hidayatullah Islamic boarding school, Surakarta.The data that has been collected and obtained is then analyzed using a structured method. Data collection was carried out by using interview, observation and documentation techniques.We strive to sort, classify and categorize all data that has been collected using guided techniques so that the themes can be identified according to the tolerance education process of the Tahfidzul Qur’an Al Kahfi Hidayatullah Islamic boarding school.The results of this study indicate the tolerance education system in the Tahfidzul Qur’an Al Kahfi Hidayatullah Islamic boarding school that tolerance education is integrated with all subjects, which the curriculum in the cottage is divided into three, namely superior subjects, special subjects and general subjects.Meanwhile, the model for implementing tolerance education includes the placement of boarding schools for students, no permanent placement of students in a hostel, stipulating regulations on the transfer of students every year and through discussion forums and halaqoh.